Pengaruh Media Audio Visual terhadap Hasil Belajar PKn Siswa Kelas III SDN Kelapa Dua Wetan 02 Ciracas - Sarah Yusria; Kasriman Kasriman (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to determine the impact of using audiovisual media (video) on students' civics education learning outcomes. The study was place in SDN Kelapa Dua Wetan 02 Ciracas during the second half of the 2023/2024 school year. Using a quasi-experimental methodology, this study employs a quantitative approach to research. The audiovisual medium itself serve as the independent variable (x), while the results of civics education serve as the dependent variable (y). Grade 3rd graders served as the sample for this research, which included both an experimental and control group. A sample approach known as purposeful sampling was used. Data collecting methods make use of test and documentation approaches. A test sheet serves as the research tool. Methods for analyzing data include both descriptive and inferential statistics, which include tests for homogeneity, hypothesis testing, and normalcy. Sig = 0.00 and t = 5.277 are the results of the independent t test. The results demonstrate that (2) learning activities using audio-visual media (learning videos) go without a hitch and (3) the use of audio-visual media influences the learning outcomes of civics.